The Role of Online and Offline Consumer Experience on Word of Mouth, Satisfaction and Brand Love - Olivas, Fernanda (2024)
The purpose of this research is to demonstrate how the online and offline consumer experience generates satisfaction, in relation to brand love. For the development of the research, a 27-item questionnaire was carried out, measured with a 5-point Likert scale, and a sample of 442 people was collected. To test the hypotheses, the structural equation model (SEM) was used and the PLS technique. Finally, the results indicate that online and offline experience has an influence on word of mouth (WOM) and satisfaction, while they both have an impact on brand love. This research contributes to the study of online and offline experience and can be used as a guide to understand omnichannel in several business.